2011
DOI: 10.5694/j.1326-5377.2011.tb03765.x
|View full text |Cite
|
Sign up to set email alerts
|

Women's uptake of Medicare Benefits Schedule mental health items for general practitioners, psychologists and other allied mental health professionals

Abstract: Objective: To quantify women's uptake of Medicare Benefits Schedule mental health items, compare characteristics of women by mental health service use, and investigate the impact on Medicare costs. Design, setting and participants: Analysis of linked survey data and Medicare records (November 2006 – December 2007) of 14 911 consenting participants of the Australian Longitudinal Study on Women's Health (ALSWH) across three birth cohorts (1921–1926 [“older cohort”], 1946–1951 [“mid‐age cohort”], and 1973–1978 [“… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 15 publications
(28 reference statements)
2
20
0
Order By: Relevance
“…37 It is also possible that women were accessing mental health services outside of the MBS, such as community health services, other GP services that are not mental health specific or services provided under the Better Outcomes in Mental Health Care program. This study shows that a higher proportion of women in major cities have accessed BAS services compared with non-urban women, with registered psychologists being the most commonly used BAS service for major citydwelling women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 It is also possible that women were accessing mental health services outside of the MBS, such as community health services, other GP services that are not mental health specific or services provided under the Better Outcomes in Mental Health Care program. This study shows that a higher proportion of women in major cities have accessed BAS services compared with non-urban women, with registered psychologists being the most commonly used BAS service for major citydwelling women.…”
Section: Discussionmentioning
confidence: 99%
“…15 The BAS, introduced under Medicare in November 2006, encourages a multi-disciplinary approach by allowing GPs to refer patients to psychologists, allied health care workers or psychiatrists and by providing a Medicare rebate for these services. [34][35][36][37][38] The current paper extends on this research by examining the uptake of BAS services in relation to area of residence. [34][35][36][37][38] The current paper extends on this research by examining the uptake of BAS services in relation to area of residence.…”
Section: Introductionmentioning
confidence: 99%
“…Other independent research has indicated that the Better Access program has failed to address key service gaps and socio‐demographic challenges, particularly affecting people living in regional and rural areas . About 60% of all services under Better Access were provided to women in 2007–08 and this has remained unchanged.…”
Section: Financial Year Of Service Services (Million) Medicare Benefimentioning
confidence: 99%
“…That study also examines the gender differences in diagnoses. A more recent survey‐based study (Byles et al. , 2011) also suggests this gender‐related problem: among women, those with low mental health “need” are consuming mental health services in Australia under Medicare and those with high mental health need are not consuming services, relatively speaking.…”
Section: Introductionmentioning
confidence: 99%
“…That study also examines the gender differences in diagnoses. A more recent survey-based study (Byles et al, 2011) those with high mental health need are not consuming services, relatively speaking. These various results strongly suggest that the extent of non-correspondence between service utilisation and ''need'' warrants further investigation.…”
Section: Introductionmentioning
confidence: 99%